Effects of seawater on UHPC: Macro and microstructure properties. (18th July 2022) - Lun Lam, Wing; Shen, Peiliang; Cai, Yamei; Sun, Yanjie; Zhang, Yangyang; Sun Poon, Chi
Highlights: Seawater affects the fresh and physical properties of UHPC due to the accelerated hydration and modified microstructure. Seawater exacerbated both the autogenous and drying shrinkage of UHPC. The pozzolanic reactivity of silica fume was enhanced, leading to higher compressive strength and autogenous shrinkage of seawater UHPC. Unlike normal concrete, seawater increased the autogenous shrinkage of UHPC. In addition, no Friedel's salt and brucite were observed in seawater UHPC but in normal concrete. Abstract: Due to the shortage of fresh water, the use of seawater in concrete production could alleviate the demand for the limited resource. To promote the use of seawater in ultra-high-performance concrete (UHPC), the effects of seawater on the hardening process and the corresponding relationship between the macroscopic performance and hydration, pozzolanic reaction, and microstructure of hydration products were investigated. Earlier setting times, higher early but lower later compressive strength and higher shrinkage of UHPC were observed. The modified performance was not only attributed to the presence of seawater accelerating the early hydration but also due to the change of microstructure and C-S-H structure. Better early strength and exacerbated shrinkage were associated with the slightly reduced porosity but refined pore structure, while lower later-age compressive strength in the seawater group was related to coarser microstructure and shorter mean chain length (MCL) and lower polymerisation of C-S-H. In addition, the pozzolanic reactivity of silica fume was enhanced, which would also contribute to the increased early compressive strength and exacerbated shrinkage of UHPC. It should be noted that no Friedel's salt and brucite were observed in the seawater UHPC. Moreover, although the incorporation of fly ash (PFA) was able to compensate for the adverse effects of seawater on compressive strength and autogenous shrinkage of UHPC, the exacerbated drying shrinkage was still a concern even when fly ash was present.